2016
DOI: 10.1007/s00704-016-2010-8
|View full text |Cite|
|
Sign up to set email alerts
|

Impacts of boreal hydroelectric reservoirs on seasonal climate and precipitation recycling as simulated by the CRCM5: a case study of the La Grande River watershed, Canada

Abstract: Located in northern Quebec, Canada, eight hydroelectric reservoirs of a 9782-km 2 maximal area cover 6.4% of the La Grande watershed. This study investigates the changes brought by the impoundment of these reservoirs on seasonal climate and precipitation recycling. Two 30-year climate simulations, corresponding to pre-and post-impoundment conditions, were used. They were generated with the fifthgeneration Canadian Regional Climate Model (CRCM5), fully coupled to a 1D lake model (FLake). Seasonal temperatures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Miller et al [21] modeled the climate changes for eight weeks in the Three Gorges Dam area and suggested that the decreased local surface and air temperature likely occurred because the reservoir acted as a potential evaporating surface. Irambona et al [22] found that reservoirs induced localized 2 m temperature warming in winter and cooling in the summer in the La Grande River watershed. Wang et al [18] revealed that the reservoir had both warming and cooling effects on the surface temperature in different parts of the dry-hot valley.…”
Section: Introductionmentioning
confidence: 99%
“…Miller et al [21] modeled the climate changes for eight weeks in the Three Gorges Dam area and suggested that the decreased local surface and air temperature likely occurred because the reservoir acted as a potential evaporating surface. Irambona et al [22] found that reservoirs induced localized 2 m temperature warming in winter and cooling in the summer in the La Grande River watershed. Wang et al [18] revealed that the reservoir had both warming and cooling effects on the surface temperature in different parts of the dry-hot valley.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical weather prediction (NWP) and climate modeling are essential tools in research and applied science applications (e.g., Bauer et al, 2015;Forster, 2017;Jacob et al, 2020). Motivated by the need to increase the reliability of climate and weather projections, the core numerical models undergo continuous improvements aiming at the best compromise between model representativity and computational efficiency (Flato et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The stored energy acts as a source to fuel evaporation during fall and at night throughout the ice‐free season (Boudreau & Rouse, 1995; Nordbo et al, 2011). These features produce distinctive diurnal and annual patterns of evaporation (Granger & Hedstrom, 2011; Heikinheimo et al, 1999; Irambona et al, 2018; Nordbo et al, 2011; Strachan et al, 2016; Venalainen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%